(3efXheI aj Yde GdMOjK hTQMgGs - (3YHO GdQMje Hf GdMSjf GdGKQjs
(3ChdgG (B:s
(3hHYO aYde GdMjK NWjQ hbYg cKjQ faYg Ydjg eOGQ CcKQ GdCMcGe hHg jYQa GdMdGd hGdMQGe hdCgdg EUWdGM dGHO ddWGdH ef ageg s
(3BNQgG (B:s
(3aef gh ef Cgd OGQjG eKdkG dg Cf jbhd ai fSHg GdOGQi hGdOeTbi hGdTGei Je GdTQM GdeHGQc s
(3GdfSNI HgG MhGTs
(3HgG eWGdYGJ cKjQIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B(9286) s
Keywords: (3GdMOjK h GdeUWdMs